Development of a profused In vitro shoot multiplication using leaf explants of Bacopa monnieri (L.) Pennell - Tata, Sape Subba (Current Botany, 2020)
Bacopa monnieri (L.) Pennell is an important medicinal plant used for the preparation of medhyarasayan (rasayana). Leaf explants of field grown young plants of B. monnieri was used to establish an efficient regeneration protocol with cytokinin (BAP) and auxin (IAA). The highest multiplication, i.e. (220 shoots/leaf, a cumulative of 2200 shoots from 10 explants) were noticed after 45 days of culture in MS medium supplemented with BAP(1.5mg/L) and IAA(0.5mg/L). The optimum concentration of growth regulator for shoot elongation and rooting was recorded in MS+GA3(0.25mg/L) and MS+IBA(1.5mg/L) respectively. The rooted plantlets were successfully established in green house conditions.